OPTIMIZATION OF MOBILE DRIVER’S LICENSE SERVICES IN IMPROVING PUBLIC SERVICES IN THE SEMARANG REGION POLICE - GUSTAFI TABARANI (Indonesian Journal of Police Studies, 2022)
Semarang Police Traffic Unit as one of the implementers of public services organized by the National Police has innovations in the administration of driver’s license services, namely mobile driver’s licenses. mobile driver’s license Semarang Police specifically provides services for driver’s license renewal. In an implementation, which has been running for some time, there are still complaints from the public. One of them is a complaint about the fees paid for the mobile driver’s license service procedure that still uses the conventional method. The results that a high potential for illegal levies/corruption practices. In writing this final project, the author uses George F. Terry's POAC management theory, SWOT analysis theory, mobile driver’s license service concept, and public service concept. This final project uses a qualitative approach and field research methods. Collecting data using interviews, observation, and document studies. The data analysis technique uses data reduction techniques, data presentation, and concluding. Based on the research result, the implementation of a mobile driver’s license registration and identification unit in improving public service in the Semarang Police is still not optimal because fees paid for mobile driver’s license service procedures still use conventional methods. Based on these results, the authors suggest that Semarang police can improve mobile driver’s license services by switching to online payments or via bank transfers to reduce the potential for illegal levies/corruption.